Memorial Names on the Map of Kharkiv - Удовенко, Лідія (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2016)
The article outlines the specificity of the Kharkiv urban memorial toponyms focusing on their peculiarities as a cultural and historical phenomenon. The origins of place names in Kharkiv are explained by means of Ukrainian linguistics facts, not just through the cultural and historical events. The author shows how Kharkiv linguistic toponyms have been created.